Movement speed of the directional crystallization front of aluminum in a cylindrical crucible under different MHD-stirring modes - Khripchenko, S.Y.; Dolgikh V.М. (Perm Federal Research Centre Journal, 2022)
To improve the quality of continuous cylindrical ingots of aluminum and its alloys produced in continuous casting machines, MHD-stirring is implemented in the hot top of the mold. For this purpose, poloidal and toroidal flows are excited in the molten metal. These flows significantly affect heat the transfer from the hot metal entering the hot top of the mold to the cooling zone, where the crystallization front is formed. The experiment showed that the toroidal flow first reduces the speed of the advance of the crystallization front, and then, as the rotating field magnitude increases, the speed ceases to change noticeably. The poloidal flow also first reduces the crystallization front speed, but somewhat faster than the toroidal flow, and there is a minimum on the curve of the dependence of the front advance speed on the traveling field magnitude, after which the crystallization front speed begins to increase. It has been found that under the combined action of travelling and rotating magnetic fields, the speed of advance of the crystallization front first decreases, and then increases.